Measurement invariance of the Dark Triad Dirty Dozen across nonclinical and clinical populations, genders, and age groups. (May 2023) - Faucher, Jonathan; Savard, Claudia; Gamache, Dominick
Abstract: Despite research linking the Dark Triad to negative mental health outcomes, data focusing on Machiavellianism, psychopathy, and narcissism altogether in clinical populations are lacking, and brief Dark Triad measures have yet to be validated in clinical populations. This study focuses on documenting the psychometric properties of the Dark Triad Dirty Dozen (DTDD) in clinical populations, and to assess measurement invariance across nonclinical and clinical populations. As secondary objectives, this study focuses on further documenting measurement invariance of the DTDD across genders and age groups. Results from a community sample ( n = 1062), a private practice clinics sample ( n = 696), and a personality disorders outpatient sample ( n = 286) confirmed measurement invariance of the DTDD across community and clinical samples, genders, and age groups. These results suggest that the construct of Dark Triad is the same across nonclinical and clinical populations, genders, and age groups, and that the DTDD is suitable to assess dark personality traits in diverse groups. Highlights: Measurement invariance of the Dark Triad Dirty Dozen is tested. Dark Triad Dirty Dozen is partially invariant across clinical and nonclinical samples. Dark Triad Dirty Dozen is gender invariant. Dark Triad Dirty Dozen is age invariant.